2004
DOI: 10.1111/j.0014-3820.2004.tb00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability and Drift Load in Populations of an Aquatic Snail

Abstract: Abstract. Population genetic theory predicts that in small populations, random genetic drift will fix and accumulate slightly deleterious mutations, resulting in reduced reproductive output. This genetic load due to random drift (i.e., drift load) can increase the extinction risk of small populations. We studied the relationship between genetic variability (indicator of past population size) and reproductive output in eight isolated, natural populations of the hermaphroditic snail Lymnaea stagnalis. In a commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 40 publications
3
35
1
Order By: Relevance
“…In addition to the now moderately large set of data on plants, two recent studies have examined the correlation between population size and fitness in animals. Puurtinen et al (2004) showed that snails from populations with less genetic diversity matured more slowly and had lower fecundity than from those populations with more genetic diversity, when reared in the laboratory environment. However, Davis and Roberts (2005) failed to find a significant effect of population size when comparing clutch size and embryonic survival in large and small populations of the frog Heleioporus albopunctatus.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the now moderately large set of data on plants, two recent studies have examined the correlation between population size and fitness in animals. Puurtinen et al (2004) showed that snails from populations with less genetic diversity matured more slowly and had lower fecundity than from those populations with more genetic diversity, when reared in the laboratory environment. However, Davis and Roberts (2005) failed to find a significant effect of population size when comparing clutch size and embryonic survival in large and small populations of the frog Heleioporus albopunctatus.…”
Section: Introductionmentioning
confidence: 99%
“…High prevalence of trematode parasitism in snail populations makes a remarkable proportion of snails infertile due to the host-castrating effect of trematodes (Dillon 2000). This may reduce the host density, as suggested by Lafferty (1993) and Puurtinen et al (2004). The current results, on the other hand, indicate that although trematode parasites should have a negative effect on snail population densities, the relationship between host density and prevalence of infection may greatly differ for individual trematode species, such as Diplostomum sp.…”
Section: Discussionmentioning
confidence: 47%
“…prevalence. This is in contrast to the negative correlation between L. stagnalis density and the prevalence of trematodes found by Puurtinen et al (2004). These authors included all trematode taxa except Diplostomum, which was absent in mid-July.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations